International Criminal Law Enforcement Mechanisms for Israel as a Perpetrator of Genocide and Crimes Against Humanity - Lisa Mery; Riri Anggriani; Resdianto Willem; Andi Sri Rezky Wulandari; St. Ulfah (Mataram Journal of International Law, 2026)
This study aims to analyze: 1) the structural challenges facing the UN and the international legal consequences of israel's violations of jus cogens obligations, alongside the implications for the global legal order and the fostering of international trust; and 2) the potential role of International Criminal Law specifically through the International Criminal Court (ICC) in addressing entities implicated in crimes evidenced empirically but which have evaded direct accountability, while also proposing strategies for international law enforcement. The research employs a normative-juridical method, utilizing approaches based on International Law, International Court of Justice rulings, and doctrines within International Criminal Law. The findings necessitate a comprehensive analysis, revealing that theoretically: 1) the failure of the legal regime to address jus cogens violations erodes the foundation of opinio juris and fosters the fragmentation of international law; and 2) israel’s proven violations and blatant display of arrogant impunity undermine state confidence in the legitimacy of International Law which ought to protect humanity thereby risking a normative collapse of the International Criminal Law regime. Consequently, there is a need for counter-hegemonic legal strategies driven by coalitions of states and non-state actors. As the UN comprises 193 member states, any action taken on its behalf must reflect the collective will of those members. Throughout the conflict involving Palestine as a nation state particularly following israel's 1948 declaration of independence the UN's inability to take appropriate humanitarian action in this protracted conflict has perpetuated the suffering of the Palestinian people to this day; this is clearly evidenced by the UN Security Council (the UN's highest body responsible for maintaining international peace and security) being repeatedly stymied by vetoes, preventing agreement on swift and effective resolutions to ensure the safety of the Palestinian people, especially in Gaza.